2003
DOI: 10.2460/ajvr.2003.64.1151
|View full text |Cite
|
Sign up to set email alerts
|

Influence of familiarity and relatedness on proximity and allogrooming in domestic cats (Felis catus)

Abstract: Familiarity and relatedness are significantly associated with allogrooming and proximity of another cat. This may be important when considering adoption of 1 or more kittens and when adding a new cat to a household in which other cats are present. Adopting small family groups may result in higher rates of affiliative behavior, stronger bonding, and lower incidence of conflict than periodically adopting single unrelated adult cats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 13 publications
1
40
0
Order By: Relevance
“…For each occurrence of an affiliative behaviour or posture, a score of +1 was assigned, and for each occurrence of an agonistic or avoidant behaviour or posture, a score of −1 was assigned. Whether a behaviour or body posture was considered affiliative, avoidant or agonistic was based on the ethogram utilised in the study of Soennichsen and Chamove (2002) and extended using the existing literature on feline body language (Bradshaw and Hall, 1999;Cameron-Beaumont, 1997;Crowell-Davis et al, 2004;Curtis et al, 2003;Karsh and Turner, 1988;Kendall and Ley, 2006;Leyhausen, 1979;Overall, 1997;Ragni and Possenti, 1990;Rodan, 2010;Rodan et al, 2011;Turner and Bateson, 2000). Each of the eight body areas handled was given two behavioural response scores for a single handling session; one for agonistic and avoidant responses and one for affiliative responses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each occurrence of an affiliative behaviour or posture, a score of +1 was assigned, and for each occurrence of an agonistic or avoidant behaviour or posture, a score of −1 was assigned. Whether a behaviour or body posture was considered affiliative, avoidant or agonistic was based on the ethogram utilised in the study of Soennichsen and Chamove (2002) and extended using the existing literature on feline body language (Bradshaw and Hall, 1999;Cameron-Beaumont, 1997;Crowell-Davis et al, 2004;Curtis et al, 2003;Karsh and Turner, 1988;Kendall and Ley, 2006;Leyhausen, 1979;Overall, 1997;Ragni and Possenti, 1990;Rodan, 2010;Rodan et al, 2011;Turner and Bateson, 2000). Each of the eight body areas handled was given two behavioural response scores for a single handling session; one for agonistic and avoidant responses and one for affiliative responses.…”
Section: Methodsmentioning
confidence: 99%
“…However, a similar effect has been shown by Gyori et al, 2010 when the familiar person was the owner; dogs exhibited more contact seeking behaviour and less gaze aversion towards their owners when their owner approached them in comparison to an experimenter, who was less familiar to them. Considering inter-cat interactions, Curtis et al (2003) found that amongst conspecifics, familiarity was significantly associated with greater amicable behaviour such as more frequent allo-grooming and increased time spent in close proximity. Thus, based on previous handler familiarity experiments and, the social behaviour of the domestic cat we would have expected cats in this study to have shown less negative behaviour when handled by their owner; a familiar person, in comparison to the experimenter; an unfamiliar person.…”
Section: Influence Of Handler Familiaritymentioning
confidence: 97%
“…This behaviour is often accompanied by head and/or flank rubbing and sniffing, but again this behaviour is not restricted to interactions with humans (Cameron-Beaumont, 1997;Mertens and Turner, 1988). Persistent close proximity or initiation of approach (with an affiliative outcome) also seems to be part of the positive social repertoire of the domestic cat to both conspecifics and humans (Mertens and Turner, 1988;Barry and Crowell-Davis, 1999;Wolfe, 2001;Curtis et al, 2003;Siegford et al, 2003).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Very little data on the exchange of grooming has been published (Kerby and Macdonald, 1988, Fig. 6.1a;van den Bos, 1998;Curtis et al, 2003), but from the limited information available it appears to be mutual within dyads, especially close relatives, and to intensify during or following minor conflict between a pair of cats. Mutual grooming may therefore be stress-reducing and (one of) the mechanism(s) whereby cats within a social group counteract their natural tendency towards competition.…”
Section: Accepted Manuscriptmentioning
confidence: 92%